Partnership in Social Marketing Programs. Socially Responsible Companies and Non-Profit Organizations' Engagement in Solving Society's Problems - Corina Şerban (Amfiteatru Economic Journal, 2011)
The development of social marketing, as an important area of analysis and research, has opened up multiple opportunities for organizations to engage in society's problems. Whether we talk about non-profit organizations engaged in health or environmental programs or private companies willing to act responsibly, their goal is a common one: to help improve people's lives by promoting responsible behaviour in society. This paper aims to extend the area of research for "cause-related marketing" by highlighting the importance of partnerships between non-profit organizations and companies based on social responsibility. As a result, the article proposes and analyzes four features of social partnership: motivation, promotion, efficiency and law effect. The study examines the Romanian consumers' opinions regarding the need of collaboration between corporations and non-profit organizations for achieving common social goals. Using the structural equation model, the paper describes the relations between each of the variables considered and social partnership and measures the extent to which these variables can influence the collaboration between organizations. The article tests and then proposes a model of the considered variables. The results obtained describe the characteristics of social partnership marketing programs and their importance for the consumer.
Keywords: M31; M14; L31; 330; partnership; cause-related marketing; social problems; non-profit organization; socially responsible company; social marketing program